2006
DOI: 10.1111/j.1365-2672.2006.02903.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental survival mechanisms of the foodborne pathogen Campylobacter jejuni

Abstract: Campylobacter spp. continue to be the greatest cause of bacterial gastrointestinal infections in humans worldwide. They encounter many stresses in the host intestinal tract, on foods and in the environment. However, in common with other enteric bacteria, they have developed survival mechanisms to overcome these stresses. Many of the survival mechanisms used by Campylobacter spp. differ from those used by other bacteria, such as Escherichia coli and Salmonella spp. This review summarizes the mechanisms by which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
197
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(202 citation statements)
references
References 98 publications
(195 reference statements)
3
197
0
2
Order By: Relevance
“…Thus, in developing countries, the routes of transmission are complex and multifactorial and campylobacteriosis in developed countries is considered mainly a food infection whose main source is the chicken meat (EFSA, 2005). Murphy et al (2006) states that the rate of campylobacteriosis incidence in the United States in 2004 was 12.9 cases per 100,000 confirmed cases of food-borne bacterial diseases in humans, whereas in the UK the rate was 73/100.000 in 2003 and in the countries of northern Europe was 60 to 90/100.000.…”
Section: Development Epidemiologymentioning
confidence: 99%
“…Thus, in developing countries, the routes of transmission are complex and multifactorial and campylobacteriosis in developed countries is considered mainly a food infection whose main source is the chicken meat (EFSA, 2005). Murphy et al (2006) states that the rate of campylobacteriosis incidence in the United States in 2004 was 12.9 cases per 100,000 confirmed cases of food-borne bacterial diseases in humans, whereas in the UK the rate was 73/100.000 in 2003 and in the countries of northern Europe was 60 to 90/100.000.…”
Section: Development Epidemiologymentioning
confidence: 99%
“…In this study, we examined the expression of all 20 drug efflux genes in E. coli under the physiological condition of anaerobiosis coupled with amino acid limitation, a typical environmental perturbation encountered by enteric bacteria in human hosts (13)(14)(15)(16). We found that among the 20 efflux genes, the Cu-sensing CusCFBA efflux system (17,18) was significantly upregulated under this physiological condition, even in the absence of copper supplement.…”
mentioning
confidence: 99%
“…As a major food-borne pathogen, C. jejuni is well adapted in its mammalian and avian hosts, as well as in food animal production environments. So that it can survive in different conditions, C. jejuni has evolved multiple strategies for adaptation, including high rates of genetic variation (mediated by mutation and horizontal gene transfer) and differential gene expression (6,11,30). Indeed, previous analyses of the genomic sequences of C. jejuni revealed the presence of multiple genes encoding regulatory functions (9,14,32,35).…”
mentioning
confidence: 99%